Combining autophagy stimulators and cellulose ethers for therapy against prion disease - Abdulrahman, Basant A. (Prion, 2019)
Prion diseases are fatal transmissible neurodegenerative disorders that affect animals and humans. Prions are proteinaceous infectious particles consisting of a misfolded isoform of the cellular prion protein PrP(C), termed PrP(Sc). PrP(Sc) accumulates in infected neurons due to partial resistance to proteolytic digestion. Using compounds that interfere with the production of PrP(Sc) or enhance its degradation cure prion infection in vitro, but most drugs failed when used to treat prion-infected rodents. In order to synergize the effect of anti-prion drugs, we combined drugs interfering with the generation of PrP(Sc) with compounds inducing PrP(Sc) degradation. Here, we tested autophagy stimulators (rapamycin or AR12) and cellulose ether compounds (TC-5RW or 60SH-50) either as single or combination treatment of mice infected with RML prions. Single drug treatments significantly extended the survival compared to the untreated group. As anticipated, also all the combination therapy groups showed extended survival compared to the untreated group, but no combination treatment showed superior effects to 60SH-50 or TC-5RW treatment alone. Unexpectedly, we later found that combining autophagy stimulator and cellulose ether treatment in cultured neuronal cells mitigated the pro-autophagic activity of AR12 and rapamycin, which can in part explain the in vivo results. Overall, we show that it is critical to exclude antagonizing drug effects when attempting combination therapy. In addition, we identified AR-12 as a pro-autophagic drug that significantly extends survival of prion-infected mice, has no adverse side effects on the animals used in this study, and can be useful in future studies.